The reality of corporate social responsibility practices in Algerian economic enterprises: A case study of the industrial equipment maintenance company in M’sila (2019–2020) - Boufenara, Hadjer; Menaceur, Abdelali (The International tax journal, 2025)
This study aims to highlight the current state of corporate social responsibility (CSR) practices within Algerian economic companies by examining the Industrial Equipment Maintenance Company in M’sila, Algeria. The study presents the various areas of the company’s social contributions, recognizing that the dimensions of CSR have diversified alongside the evolution of corporate activities, resulting in a broad range of implementable fields. The findings indicate that the Industrial Equipment Maintenance Company in M’sila focuses its social contributions on four main areas: first, employee-related practices, involving the diversification of compensation packages and benefits to enhance employee loyalty and commitment; second, client-oriented efforts, aimed at expanding its customer base through delivering high-quality services and broadening its engagement with clients; third, societal roles, including creating employment opportunities, contributing to reducing unemployment rates, and supporting scientific research in collaboration with various academic institutions; and finally, environmental responsibility, demonstrated by the proper disposal of environmentally harmful waste through specialized technical methods within appropriate timeframes.